Vitamin D Deficiency and Sleep Quality in Minority Pregnant Women. Issue 3 (May 2020) - Woo, Jennifer; Penckofer, Susan; Giurgescu, Carmen; Yeatts, Paul E.
Abstract: Purpose: To examine if vitamin D deficiency was associated with poor sleep quality in a sample of African American and Hispanic pregnant women. We also examined if race moderates the relationship between serum 25(OH)D levels and sleep quality among participants in this sample. Study Design and Methods: Using a cross-sectional design, a sample of 115 African American and Hispanic pregnant women were enrolled from a federally qualified health center in the Midwest. Women completed questionnaires and had blood drawn for serum 25(OH)D levels between 24- and 32 weeks gestation. The questionnaires included demographic characteristics, the Pittsburgh Sleep Quality Index, and dietary vitamin D and calcium intake. Results: The overall regression model indicated that the predictors explained 17% of variance in sleep quality ( F (5, 103) = 4.10, p = .002, R 2 = 0.17). Serum 25(OH)D levels were significant predictors of sleep quality after controlling for covariates (i.e., race, maternal age, prepregnancy body mass index, gestational age at data collection). Race did not moderate the association between serum 25(OH)D levels and sleep quality among women in this sample. Clinical Implications: Pregnant women should be screened for vitamin D deficiency. Women who have vitamin D deficiency should be provided vitamin D supplementation. Vitamin D supplementation may be a simple solution to enhance sleep quality at this critical time in a woman's life. Abstract : Researchers evaluated the relationships between vitamin D deficiency and sleep quality among pregnant African American and Hispanic women. Minority women are at higher risk for vitamin D deficiency and more likely to experience poor sleep quality compared with non-Hispanic White women. Over 60% of women in this study had vitamin D deficiency and 58% had poor sleep quality scores. Low vitamin D levels were associated with poor sleep quality. All pregnant women should be assessed for sleep quality and sleep hygiene techniques should be recommended as appropriate.